Relative Abundance, Frequency And Dominance Of Flies In Several Traditional Market At Martapura District - Trianto, Manap; Marisa, Fajri; Siswandari, Ni Putu (Metamorfosa: Journal of Biological Sciences, 2020)
Flies are insects that live close to the human environment. Flies around the settlement were many and carry a variety of diseases that can danger the public health. Research purpose is to determine the relative abundance, frequency and dominance of flies in several traditional markets at Martapura District. This research was conducted in five traditional markets, namely Sejumput market, Batuah market, Sekumpul market, Permata market, and Kuliner market in April to May 2020. Flies were collected using a sweep net by swinging it around the landfills. The collected flies were then identified using identification keys. Results showed there were four species of flies in research location, that are Musca domestica, M. cinducens, Chrysomya megacephala , and C. rufifacies . The relative abundance, species frequency and species dominance signified that the capturing of M. domestica flies is the highest. Furthermore, Batuah market location have the highest amount of relative abundance, species frequency, and species dominance of flies compared to other locations. This research is useful as preliminary information in determining the potential of flies as a vector of disease transmission in an environment.       Keyword : relative abundance, frequency, dominance, type of flies, traditional market